2022
DOI: 10.1088/1361-651x/ac6e7b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of fatigue behavior of nickel single-crystal under cyclic shear deformation and hyper-gravity condition

Abstract: Dynamic mechanical properties play an essential role in governing the intrinsic fatigue behavior of superalloys. In this work, [001](010), [110](-110), and [101](010) pre-existing center cracks model of nickel single crystals under increasing cyclic shear deformations were studied by molecular dynamics simulations. More importantly, we introduced three hyper-gravity forces, i.e., 3⨯1012 g, 4⨯1012 g, and 5⨯1012 g, during the fatigue deformation to simulate the high-speed rotation of the blade. The stress intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To generate the hyper-gravity environment at the atomic scale, we introduced a constant force that pointed along the hyper-gravity direction to each atom. Recently, such a hyper-gravity loading scheme has been reported by molecular dynamics and phase-field simulations [21,28]. In addition, the effect of rotation that introduces too many variables and makes the analysis difficult is ignored.…”
Section: Crack Model Analysis Under Zero-gravity Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate the hyper-gravity environment at the atomic scale, we introduced a constant force that pointed along the hyper-gravity direction to each atom. Recently, such a hyper-gravity loading scheme has been reported by molecular dynamics and phase-field simulations [21,28]. In addition, the effect of rotation that introduces too many variables and makes the analysis difficult is ignored.…”
Section: Crack Model Analysis Under Zero-gravity Conditionsmentioning
confidence: 99%
“…Zhou et al [20] extracted the da/dN metrics from the fatigue crack growth in polycrystal coherent twins. Recently, we applied hyper-gravity loading to study the fatigue behavior of nickel under cyclic shear deformation [21]. The critical stress is strongly dependent on the hyper-gravity intensities and temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was attributed to the fact that higher temperatures make it easier to break atomic bonds, leading to lower resistance to crack propagation 17 . Xiao et al 18 revealed that the stress intensity factor K showed a strong temperature dependence during crack propagation. In addition, Tang et al 19 observed that the FCGR of magnesium decreased with increasing temperature and strain rate along a specific orientation.…”
Section: Introductionmentioning
confidence: 99%